A Penicillin Derivative Exerts an Anti-Metastatic Activity in Melanoma Cells Through the Downregulation of Integrin αvβ3 and Wnt/β-Catenin Pathway - Barrionuevo, Elizabeth; Cayrol, Florencia; Cremaschi, Graciela A.; Cornier, Patricia G.; Boggián, Dora B.; Delpiccolo, Carina M. L.; Mata, Ernesto G.; Roguin, Leonor P.; Blank, Viviana C. (Frontiers in Pharmacology, 2020)
The synthetic triazolylpeptidyl penicillin derivative, named TAP7f, has been previously characterized as an effective antitumor agent in vitro and in vivo against B16-F0 melanoma cells. In this study, we investigated the anti-metastatic potential of this compound on highly metastatic murine B16-F10 and human A375 melanoma cells. We found that TAP7f inhibited cell adhesion, migration and invasion in a dose-dependent manner. Additionally, we demonstrated that TAP7f downregulated integrin αvβ3 expression and Wnt/β-catenin pathway, a signaling cascade commonly related to tumor invasion and metastasis. Thus, TAP7f reduced both the enzymatic activity and the expression levels of matrix-metalloproteinases -2 and -9 in a time dependent manner. Moreover, TAP7f inhibited the expression of the transcription factor Snail and the mesenchymal markers vimentin, and N-cadherin, and up-regulated the expression of the epithelial marker E-cadherin, suggesting that the penicillin derivative affects epithelial-mesenchymal transition. Results obtained in vitro were supported by those obtained in a B16-F10-bearing mice metastatic model, that showed a significant TAP7f inhibition of lung metastasis. These findings suggest the potential of TAP7f as a chemotherapeutic agent for the treatment of metastatic melanoma.